2019
DOI: 10.1002/jcb.29323
|View full text |Cite
|
Sign up to set email alerts
|

miR‐605‐5p promotes invasion and proliferation by targeting TNFAIP3 in non–small‐cell lung cancer

Abstract: Lung cancer is an significant cause of death worldwide, and non–small‐cell lung cancer (NSCLC) is the most common type of lung cancer. MicroRNAs (miRNAs) have been identified to play key roles in NSCLC development. Recently, it has been reported that miR‐605‐5p is a cancer‐related miRNA in several types of tumors. In this study, we study the role of miR‐605‐5p in NSCLC cells. We find that miR‐605‐5p is upregulated in NSCLC cells. Overexpression of miR‐605‐5p significantly promotes lung cancer invasion and migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Invasion and metastasis are the main causes of poor prognosis and high mortality rate in patients with lung cancer (4). Although great efforts, such as the identification of novel biomarkers, establishment of modified operations and development of specific drugs, have been made in the clinical setting, the postoperative survival rate of patients has not significantly improved (5,6). Therefore, it is of great clinical significance to explore the molecular mechanisms underlying the progression of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Invasion and metastasis are the main causes of poor prognosis and high mortality rate in patients with lung cancer (4). Although great efforts, such as the identification of novel biomarkers, establishment of modified operations and development of specific drugs, have been made in the clinical setting, the postoperative survival rate of patients has not significantly improved (5,6). Therefore, it is of great clinical significance to explore the molecular mechanisms underlying the progression of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…However, as far as we know, there are limited studies towards the identified miRNAs in HPV-signature. A research implied that miR-605-5p promoted proliferation and invasion of non-small-cell lung cancer cell carcinoma via sponging TNFAIP3 ( 48 ). It was reported miR-135b-3p could inhibit cell clonogenicity and metastasis in triple-negative breast cancer by targeting RGMA ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-605 also functions as a tumor suppressor in melanoma by regulating the expression of inositol polyphosphate-4-phosphatase type II B ( 35 ). In addition, miR-605 was also demonstrated to affect the proliferation, migration and invasion of non-small cell lung cancer, prostate cancer, and breast cancer ( 18 , 19 , 36 ). In the present study, miR-605 was found to be a vital factor in the progression of OS, as the downregulation of miR-605 significantly promoted cell proliferation, migration, and invasion of OS, which indicates that miR-605 may be involved in the progression and development of OS.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the expression and function of miR-605 were investigated in OS tissues and cells in vitro, however, the role of miR-605 in the progression and prognosis of OS should be verified in in vivo experiments. On the other hand, previous studies have provided some potential targets of miR-605, such as tumor necrosis factor α-induced protein 3, EN2, enhancer of zeste 2 (EZH2) and forkhead Box P1, which mediate the functional effects of miR-605 in human malignancies ( 18 , 19 , 37 , 38 ). EZH2 is a widely investigated oncogene in several human malignancies, such as non-small cell lung cancer and bladder cancer ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation